Comparison between unit cell and plane strain models of stone column ground improvement - Gaber, Maryam; kasa, Anuar; Abdul Rahman, Norinah; Alsharef, Jamal (International Journal of Engineering and Technology, 2018)
This article presents a comparative study of the behaviour of clayey soil reinforcements using stone column ground improvement by means of numerical analyses. Two-dimensional finite element analyses with commercially available software, PLAXIS, were performed on end-bearing stone columns using 15-noded triangular elements to investigate the impact of the modelling type on the stress concentration ratio and failure mechanism of an improved foundation system. Consolidation analyses were conducted throughout the study using Mohr-Coulomb’s criterion. The computed values of the stress concentration ratios were compared for different key parameters, including the diameters of stone columns, c/c spacing of columns, friction angle of stone column material, and undrained cohesion of soft soil. The major conclusions of this study were that the stone column in the unit cell model shared between 2.5 to 3.14 times more loads than the surrounding soil, whilst in the plane strain model it shared between 1.7 to 2.9 times more loads. The use of plane strain approach to model the stone column gave a more comprehensive representation of the stress distribution and load transfer between the soil and columns, in addition to being a better method than the unit cell concept to evaluate the failure mode in this system.